2020
DOI: 10.3390/ma13245704
|View full text |Cite
|
Sign up to set email alerts
|

Doping Effect on Cu2Se Thermoelectric Performance: A Review

Abstract: Cu2Se, owing to its intrinsic excellent thermoelectric (TE) performance emerging from the peculiar nature of “liquid-like” Cu+ ions, has been regarded as one of the most promising thermoelectric materials recently. However, the commercial use is still something far from reach unless effective approaches can be applied to further increase the figure of merit (ZT) of Cu2Se, and doping has shown wide development prospect. Until now, the highest ZT value of 2.62 has been achieved in Al doped samples, which is twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 104 publications
(124 reference statements)
1
22
0
Order By: Relevance
“…Hence, many efforts have been carried out to further improve ZT values by adjusting the content of Cu vacancies in the past few decades . Element doping has been proven to be one of the most effective approaches to improve the TE performance of Cu 2 Se-based materials . It was reported that doping metal elements (such as Ga, Ni, Al, Br, and so on) can optimize effectively the hole concentration and significantly improve the TE performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, many efforts have been carried out to further improve ZT values by adjusting the content of Cu vacancies in the past few decades . Element doping has been proven to be one of the most effective approaches to improve the TE performance of Cu 2 Se-based materials . It was reported that doping metal elements (such as Ga, Ni, Al, Br, and so on) can optimize effectively the hole concentration and significantly improve the TE performance.…”
Section: Introductionmentioning
confidence: 99%
“…37 Element doping has been proven to be one of the most effective approaches to improve the TE performance of Cu 2 Se-based materials. 38 It was reported that doping metal elements (such as Ga, Ni, Al, Br, and so on) 39−41 can optimize effectively the hole concentration and significantly improve the TE performance. For example, Bailey et al reported a ZT ∼ 1 at 823 K in 1% Sn-doped Cu 2 Se samples.…”
Section: ■ Introductionmentioning
confidence: 99%
“…30 To further improve the ZT values, nanostructure engineering and elemental doping are considered to be the effective strategies. [35][36][37] The output voltage test of the sintered-Cu 2Àx Se sample was then investigated at 303 K. Fig. 5(a) shows the voltage-time curve of the sintered sample during heating.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that Cu 2 Se has an excellent intrinsic TE performance, however, practice shows that alloying with other elements can greatly improve the thermoelectric characteristics of copper selenide. Doping effect on Cu 2 Se thermoelectric performance was reviewed in 2020 by Y. Qin et al [ 202 ]. The authors summed that through doping, many elements, such as Al, Li, Na, In, etc., have caused the ZT value of Cu 2 Se to exceed 2, and almost break through the minimum requirement of commercial use ( ZT > 3).…”
Section: Transport Phenomena In Mixed Electron–ion Conductorsmentioning
confidence: 99%